Experimental study on creep behaviors of red sandstone in Sichuan and Chongqing under acid corrosion - Ni Xie; Dinghao Wang; Yang Lü; Qing Gao (地质科技通报, 2022)
The creep characteristics of rock have an important effect on the long-term stability of rock engineering. Especially under the action of acid rain and other water chemistry, the rock microstructure is destroyed, and the creep characteristics and deformation are more significant. With the red sandstone of the Erfo Temple in Chongqing as the research object, the creep characteristics of sandstone under acid corrosion are studied by triaxial compression creep test. The results show that the porosity of sandstone increases with acid corrosion and immersion, which leads to the large instantaneous strain and creep of sandstone under the first stage load, and then the instantaneous strain and creep increase with the increase in stress. The creep strength is 76% of the compressive strength, and the long-term strength is only 54% of the compressive strength. To describe the whole creep process, a damage creep model is established to fit the test data, and its applicability is verified, which provides a reference for geotechnical engineering construction.